La democracia directa como alternativa a la democracia representativa: algunas lecciones desde la experiencia suiza - Eduardo J. Ruiz Vieytez (Revista Vasca de Administración Pública)
In the last years, several social and political sectors have suggested a more frequent and efficient use of referendum as a mechanism for political participation and democratic regeneration in our system. Within the European context, Switzerland is the country that most frequently uses the referendum. Its experience shows that a frequent use of referendum is not free from political and legal problems. Among the political concerns, it can be mentioned ta low turnout, an emerging populism and a peculiar political culture that enshrines popular will even in the cases in which this might go against human rights. From the legal perspective, important difficulties can be found when clauses adopted by referendum go against international legal standards, particularly in the field of human rights. These problematic factors must be seriously considered in a possible increase of the use of referendum in our constitutional system.